Enhanced magnetorheological performance of highly uniform magnetic carbon nanoparticles - Lee, Seungae; Shin, Keun-Young; Jang, Jyongsik (ROYAL SOC CHEMISTRY, 2015)
Magnetic carbon nanoparticles (MC NPs) are prepared on a multi-gram scale through carbonization of iron-doped polypyrrole nanoparticles (PPy NPs). Three different-sized MC NPs (ca. 40, 60 and 90 nm) are prepared and adopted as dispersing materials for magnetorheological (MR) fluids to investigate the influence of particle size on MR properties. The MC NP-based MR fluids exhibit outstanding MR performances compared to the conventional magnetic carbon material-based fluids. In addition, the MR activities are enhanced with decreasing particle diameter and increasing applied magnetic field strength. Furthermore, anti-sedimentation properties are examined in order to achieve in-depth insight into the effect of the particle size on MR fluids.
Keywords: IRON PARTICLES; CONDUCTING POLYMER; FACILE SYNTHESIS; POLYPYRROLE; NANOTUBES; FLUIDS; FABRICATION; COMPOSITE; SURFACE; STABILIZATION